Keluarga sebagai ecclesia domestica: Fondasi teologis-biblis pengembangan kecerdasan emosional anak dalam pengasuhan kristiani - Gidion; Herman Poroe (KURIOS, 2025)
The crisis of emotional regulation in the contemporary generation demands a reconceptualization of the Christian parenting paradigm. This research examines the concept of ecclesia domestica as a theological foundation for the development of children's emotional intelligence. Through a practical and constructive theological approach, this study synthesizes patristic thought on the family as a "little church" with contemporary emotional intelligence theory. Analysis focuses on four dimensions: the sacramentality of domestic space, koinonia as a matrix for emotional formation, family liturgy in affective regulation, and the missio Dei in transformative parenting. Findings indicate that the ecclesia domestica conception provides a robust theological framework for integrating spirituality and emotional development. Practical implications include reorienting parenting from an instructive to a formative-relational model, where the family functions as a hermeneutical community, facilitating children's encounter with God's love through secure attachment experiences. This research contributes to the development of holistic and contextual family theology for the digital era.   Abstrak Krisis regulasi emosional pada generasi kontemporer menuntut rekonseptualisasi paradigma pengasuhan Kristiani. Penelitian ini mengeksplorasi konsep ecclesia domestica sebagai fondasi teologis untuk pengembangan kecerdasan emosional anak. Melalui pendekatan teologi praktis-konstruktif, studi ini mensintesiskan pemikiran patristik tentang keluarga sebagai "gereja kecil" dengan teori kontemporer emotional intelligence. Analisis difokuskan pada empat dimensi: sakramentalitas ruang domestik, koinoniasebagai matriks pembentukan emosi, liturgi keluarga dalam regulasi afektif, dan missio Dei dalam pengasuhan transformatif. Temuan menunjukkan bahwa konsepsi ecclesia domestica menyediakan kerangka teologis yang robust untuk mengintegrasikan spiritualitas dan perkembangan emosional. Implikasi praktis mencakup reorientasi pengasuhan dari model instruktif menuju formatif-relasional, di mana keluarga berfungsi sebagai komunitas hermeneutis yang memfasilitasi perjumpaan anak dengan kasih Allah melalui pengalaman kelekatan yang aman. Penelitian ini berkontribusi pada pengembangan teologi keluarga yang holistik dan kontekstual untuk era digital.